High current density, low threshold field emission from functionalized carbon nanotube bucky paper - Kakade, Bhalchandra A.; Pillai, Vijayamohanan K.; Late, Dattatray J.; Chavan, Padmakar G.; Sheini, Farid J.; More, Mahendra A.; Joag, Dilip S. (Applied Physics Letters, 2010)
Field emission studies of bucky paper of multiwalled carbon nanotubes (MWNTs), prepared after microwave (MW) assisted acid functionalization are reported along with a comparison with that of ``as-grown'' sample. MW treated bucky papers reveal an interesting linear field emission behavior in Fowler-Nordheim plot. The field emission currents at preset value are found to be remarkably stable over a period of more than 3 h sustaining current densities of 4.9 mA/cm(2) and 8.5 mA/cm(2) for ``as-grown'' and functionalized sample, respectively. The enhancement in the field emission due to functionalization has been discussed in terms of tip opening and defect induced charge transport caused by intershell and intertubular interaction. (C) 2010 American Institute of Physics. [doi:10.1063/1.3479049]
Keywords: Carbon nanotubes; current density; field emission; fullerenes

High efficiency electron field emission from protruded graphene oxide nanosheets supported on sharp silicon nanowires - Devarapalli, Rami Reddy; Kashid, Ranjit V.; Deshmukh, Ashvini B.; Sharma, Ponchami; Das, Manash R.; More, Mahendra A.; Shelke, Manjusha V. (Journal of Materials Chemistry C, 2013)
Graphene oxide (GO) potentially has applications in vacuum microelectronic devices for realization of field emission displays. Graphene and its derivatives are expected to be efficient field emitters due to their unique electrical properties. However, the flat sheet structure of graphene or GO allows electron field emission only from the edges of graphene and GO nanosheets. In order to extract maximum field emission current density at lower applied voltage from the GO nanosheets, we supported and stretched them on sharp tips of silicon nanowires (SiNWs). Highly efficient and stable field emission with low turn-on field was observed for these SiNW-GO heterostructures. The sharp protrusions created by stretching of the GO nanosheets on SiNWs locally enhance the electric field and thus enhance the field emission characteristics. The dominant use of silicon in electronic devices makes this approach robust for the development of field emission devices using graphene based field emitters.

High-performance field emission device utilizing vertically aligned carbon nanotubes-based pillar architectures - Gupta, Bipin Kumar; Kedawat, Garima; Gangwar, Amit Kumar; Nagpal, Kanika; Kashyap, Pradeep Kumar; Srivastava, Shubhda; Singh, Satbir; Kumar, Pawan; Suryawanshi, Sachin R.; Seo, Deok Min; Tripathi, Prashant; More, Mahendra A.; et al. (AIP Advances, 2018)
The vertical aligned carbon nanotubes (CNTs)-based pillar architectures were created on laminated silicon oxide/silicon (SiO2/Si) wafer substrate at 775 degrees C by using water-assisted chemical vapor deposition under low pressure process condition. The lamination was carried out by aluminum (Al, 10.0 nm thickness) as a barrier layer and iron (Fe, 1.5 nm thickness) as a catalyst precursor layer sequentially on a silicon wafer substrate. Scanning electron microscope (SEM) images show that synthesized CNTs are vertically aligned and uniformly distributed with a high density. The CNTs have approximately 2-30 walls with an inner diameter of 3-8 nm. Raman spectrum analysis shows G-band at 1580 cm(-1) and D-band at 1340 cm(-1). The G-band is higher than D-band, which indicates that CNTs are highly graphitized. The field emission analysis of the CNTs revealed high field emission current density (4mA/cm(2) at 1.2V/mu m), low turn-on field (0.6 V/mu m) and field enhancement factor (6917) with better stability and longer lifetime. Emitter morphology resulting in improved promising field emission performances, which is a crucial factor for the fabrication of pillared shaped vertical aligned CNTs bundles as practical electron sources. (c) 2018 Author(s).